Ametsuchi : Photographs by Rinko Kawauchi - Kawauchi, Rinko; Ciccotti, Susan (NY; Aperture Foundation Books, 2013)
Rinko Kawauchi has gained international recognition for her nuanced, lushly colored images that offer closely observed fragments of everyday life. In her latest work, she shifts her attention from the micro to the macro. The title, "Ametsuchi," is composed of two Japanese characters meaning "heaven and earth," and is taken from the title of one of the oldest pangrams in Japanese-a chant in which each character of the Japanese syllabary is used. Translated loosely as "Song of the Universe," it comprises a list that includes the heavens, earth, stars and mountains. In "Ametsuchi," Kawauchi brings together images of distant constellations and tiny figures lost within landscapes, as well as photographs of a traditional controlled burn farming method ("yakihata") in which the cycles of cultivation and recovery span decades and generations. Punctuating the series are images of Buddhist rituals and other religious ceremonies-a suggestion of other means by which humankind has traditionally attempted to transcend time and memory. The book is designed by award-winning Dutch designer Hans Gremmen, who brings a sense of the monumental and the mysterious to the design, including a seductive origami binding. The series is Kawauchi's first to be fully realized with a medium-format, 4 x 5 camera, instead of the 2- -inch format for which she has become best known. Rinko Kawauchi (b. 1972 in Shiga, Japan) has had solo exhibitions at Fondation Cartier, Paris; Photographers Gallery, London; and Tokyo Metropolitan Museum of Photography; among other venues. She was shortlisted for the 2012 Deutsche Börse Photography Prize. She lives and works in Tokyo.
English
Keywords: TR624-835 Technology- Applied Photography